Medical training in private and public. (6th August 2019) - Phillips, Stephanie; Xia, Vivianne; Zhuang, Donna; Klein, Linda
Summary: Background: Globally, the need for medical student training to be undertaken in the private sector is likely to increase. In Australia, it has increased by 250 per cent in the last decade. Effective clinical education is highly dependent on the attitudes and willingness to participate of both patients and medical staff. We aimed to examine these attitudes in both private and public hospitals. Methods: Patients and medical staff at a private and a public hospital in Sydney were surveyed during December 2016 and January 2017 to investigate attitudes to medical student training. Attitudes were compared between hospitals. We also compared recent attitudes in the private hospital with those obtained in 2012. Results: Patients at the public hospital were significantly more likely to want a student present at a consultation than those at a private hospital. Public hospital doctors had more positive attitudes towards medical students than their private colleagues. The negative financial impact of teaching was more significant for those in private practice. Since 2012, attitudes of private hospital patients towards medical students became significantly more positive whereas doctors' attitudes became less positive. The expansion of clinical education into the private sector is likely to increase globally Discussion: The willingness of patients to participate in medical student training in both public and private hospitals is encouraging for future expansion into the private sector. The reduced willingness amongst private hospital medical staff over time and, in comparison to public hospital staff, suggests a need to address barriers for staff in the private sector.